2013
DOI: 10.5194/npg-20-1001-2013
|View full text |Cite
|
Sign up to set email alerts
|

Parameter variations in prediction skill optimization at ECMWF

Abstract: Abstract. Algorithmic numerical weather prediction (NWP) skill optimization has been tested using the Integrated Forecasting System (IFS) of the European Centre for MediumRange Weather Forecasts (ECMWF). We report the results of initial experimentation using importance sampling based on model parameter estimation methodology targeted for ensemble prediction systems, called the ensemble prediction and parameter estimation system (EPPES). The same methodology was earlier proven to be a viable concept in low-orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Although parameter covariances for IFS are available from research experiments (Ollinaho et al , ), how to apply them effectively still remains an open question (as was indicated by the experiments of Christensen et al , ). We also note that multiple space and time correlation scales that differ from parameter to parameter are technically possible (according to the multiple scales in SPPT; Palmer et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Although parameter covariances for IFS are available from research experiments (Ollinaho et al , ), how to apply them effectively still remains an open question (as was indicated by the experiments of Christensen et al , ). We also note that multiple space and time correlation scales that differ from parameter to parameter are technically possible (according to the multiple scales in SPPT; Palmer et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…For the upper-troposphere zonal wind, the improvements (9 %) in skill are substantial when compared to other stateof-the-art stochastic perturbation schemes. In Ollinaho et al (2017) improvements by the SPP and SPPT scheme around 2.5 % are reported for zonal wind at 200 hPa. For 850 hPa zonal wind CRPS improvements induced by the SPP and SPPT scheme (1.8 %) are also comparable to the results presented here (1.7 %).…”
Section: Ic and Lbc Perturbationsmentioning
confidence: 96%
“…This technique was first applied in Bowler et al (2008) and further adapted for use in a convection-permitting ensemble by Baker et al (2014). The concept of stochastically perturbing parameters was further generalized in the stochastically perturbed parameterization (SPP) scheme (Ollinaho et al, 2013(Ollinaho et al, , 2017. SPP extends the concept of perturbing parameters to locally perturbing both parameters and variables inside the parameterizations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ollinaho et al . () describe the use of a Bayesian parameter estimation framework to quantify the uncertainty in four parameters within the convection parametrisation scheme, which was used by Christensen et al . () to develop a well‐constrained stochastically perturbed parameter scheme.…”
Section: Introductionmentioning
confidence: 97%